KAHOOT! IN TEACHING VOCABULARY TO SEVENTH GRADERS OF JUNIOR HIGH SCHOOL - Salsabilla Fitrotun Nada; Wiwiet Eva Savitri (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
The research investigates Kahoot!'s effectiveness in teaching vocabulary to junior high school pupils. According to observation by the researcher at a private Islamic junior high school, English language learners frequently struggled with vocabulary deficiency when learning English. In addition, the teacher frequently referred to textbooks, which was tiresome and repetitive for seventh-grade students. A promising way to address these issues was to deploy the educational platform termed Kahoot! The end goal of the present research was to ascertain whether or not Kahoot! showed its effectiveness in vocabulary teaching to junior high school seventh graders. The study utilized a quantitative methodology and was designed as a quasi-experimental design with a pre-test and a post-test as instruments. An independent sample t-test was applied. This research focused on sixty students as the subjects. Based on the data analysis, a statistically significant distinction was proven by the p-value= .000. The experimental group exhibited supreme performance with a score of 76.5 in contrast to the control group with only 55.5. The score for the effect size of teaching vocabulary using Kahoot about directions material was 0.5, showing a large effect. It can be inferred that Kahoot! demonstrates its effectiveness in teaching vocabulary to seventh graders of junior high school.